Air pollution and point sources investigations in Erzurum - Kirimhan, S. (My University, 1991)
Between April 1984 and January 1986, air quality measurements were made at five designated sites in the city. The analyzed data showed that recent sulfur dioxide concentration decreased to 31% of the older values. The average value of sulfur dioxide concentration was 290 ?g/m3 in the winter of 1985-1986. In this research period, the most of the air pollution was obtained during the months of January. The highest value of sulfur dioxide concentration was obtained as 1299 ?g/m3, on January 24, 1985. As sulfur dioxide, 22% of the daily average values was found to be higher than standards given by Turkish Air Quality Standards. The same ratio was 17% for nitrogen dioxide and 11% for particulate matter. -from English summary
Erzurum'da hava kirliligi ve nokta kaynak arastirmasi
Keywords: Erzurum; Turkey; air quality measurement; nitrogen dioxide; particulate matter; pollution; sulphur dioxide